Meningkatkan Aktivitas Dan Hasil Belajar Materi Siklus Air Menggunakan Model Lemper - Silvy Norazizah; Muhammad Saleh (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
The problem in this study is the low student learning activity which has an impact on low learning outcomes in class V SDN Pangeran 2 Banjarmasin. The purpose of this study was to describe teacher activities, analyze student activities, and analyze student learning outcomes. This study uses a qualitative and quantitative approach to the type of Classroom Action Research. Data analysis techniques in the form of observation sheets and learning outcomes. The data were generated from observation instrument sheets and learning achievement tests, then analyzed using descriptive techniques and described in the form of tables and graphs. The results showed that teacher activity at meeting I obtained a score of 27 at meeting IV increased to 35. Student activity at meeting I reached 42% increased at meeting IV to 100%. Student learning outcomes at meeting I obtained 42% and increased at meeting 4 to 100%. Based on the results of this study it can be concluded that the use of the LEMPER model can increase teacher activity, student activity, and learning outcomes.